Physical Activity Level in Children and Adolescents with Type 1 Diabetes: a cross-sectional study - Sara Sofia Pereira Santos (2022)
Background: Type 1 Diabetes Mellitus (T1DM) carries a high risk for the development of several chronic systemic complications, being of vital importance its adequate management, balancing physical activity (PA) practice, diet, and insulin regimen. Nonetheless, some factors may be a barrier to regular PA in diabetic patients, as fear of hypoglycemia. Additionally, PA direct impact in T1DM is still poorly understood. Objectives: Therefore, we aimed to compare physical activity level (PAL) between children and adolescents with T1DM and healthy controls, as well to report other factors which may affect PA in youth. Materials and Methods: A total of 86 participants (T1DM=61, control=25) were included. Data was collected through a questionnaire, applied to patients that recurred to CHUSJ between December 2021 and January 2022. Results: No significant differences were found regarding PAL when comparing T1DM youth with healthy peers (1.470 vs. 1.469 METs/min, p=0.964). In T1DM group, a positive correlation was found between PAL and HbA1c (r=0.254, p=0.048). Conclusions: Our findings suggest that diabetes-associated barriers do not play a significant role limiting PA routines in diabetic youth, since reported PAL was similar in both groups. This study emphasized the necessity of overcoming questions related to PA in T1DM patients, in an attempt to attain from physical activity the maximum benefit.